2013
DOI: 10.1016/j.mrfmmm.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

DNA–protein crosslinks processed by nucleotide excision repair and homologous recombination with base and strand preference in E. coli model system

Abstract: Bis-electrophiles including dibromoethane and epibromohydrin can react with O6-alkylguanine-DNA alkyltransferase (AGT) and form AGT-DNA crosslinks in vitro and in vivo. The presence of human AGT (hAGT) paradoxically increases the mutagenicity and cytotoxicity of bis-electrophiles in cells. Here we establish a bacterial system to study the repair mechanism and cellular responses to DNA-protein crosslinks (DPCs) in vivo. Results show that both nucleotide excision repair (NER) and homologous recombination (HR) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…While we have shown that PrimPol re-priming initiates HR at UV, 4-NQO, and BPDE DNA adducts, it will be interesting to investigate whether other bulky lesions or replication impediments can be channeled into this pathway. DNA-protein crosslinks, for example, engage HR for repair 45 , 46 and lead to template-switching 47 raising the question of whether PrimPol could act at these lesions as well. PrimPol also re-primes at R-loops and secondary structure-forming sequences 48 , 49 , opening up the possibility that HR in those backgrounds might depend at least partially on PrimPol.…”
Section: Discussionmentioning
confidence: 99%
“…While we have shown that PrimPol re-priming initiates HR at UV, 4-NQO, and BPDE DNA adducts, it will be interesting to investigate whether other bulky lesions or replication impediments can be channeled into this pathway. DNA-protein crosslinks, for example, engage HR for repair 45 , 46 and lead to template-switching 47 raising the question of whether PrimPol could act at these lesions as well. PrimPol also re-primes at R-loops and secondary structure-forming sequences 48 , 49 , opening up the possibility that HR in those backgrounds might depend at least partially on PrimPol.…”
Section: Discussionmentioning
confidence: 99%
“…While we have shown that PrimPol re-priming initiates HR at UV, 4-NQO and BPDE DNA adducts, it will be interesting to investigate whether other bulky lesions or replication impediments can be channelled into this pathway. DNAprotein crosslinks for example engage HR for repair 41,42 and lead to templateswitching 43 raising the question whether PrimPol could act at these lesions as well. PrimPol also re-primes at R-loops and secondary structure-forming sequences 44,45 , opening up the possibility that HR in those backgrounds might depend at least partially on PrimPol.…”
Section: Discussionmentioning
confidence: 99%
“…Immobilized proteins onto DNA are described to be very effective disruptors of transcription [ 37 ], and are preferentially repaired if they are in the transcribed strand [ 38 ]. The arrest of RNApol II at transcription blocking lesions stops the elongation of the newly synthesized RNA and if the block is prolonged in time, leads into apoptosis.…”
Section: Discussionmentioning
confidence: 99%